Resor Pantai Ogis Muara Bono Di Pelalawan Dengan Pendekatan Arsitektur Pesisir - Windy Nurjana; Ratna Amanati; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pelalawan has several attractions, and Bono Waves in Ogis Beach Village Teluk Meranti Sub-district is one of them. However, these attractions are not supported by sufficient facilities, one of which is a residential resort. This design has a close connection with the resort destination in Ogis Beach that is with Coastal Architecture Approach. In addition, the design of tourist attraction area Ogis Beach Beach Bono will apply the concept of